Islam and the Relation of Religions JalÈƒlain's Perspective and Its Implementation in the Multicultural Life of Sam Poo Kong and Soen Ang Ing Societies - Inayah, Inayah; Husna, Muhammad Ahsanul; Sumbulah, Umi; Smeer, Zeid B (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
The phenomenon of Islam and the relationship of its true religions already exists and is exemplified directly in the life of the Prophet SAW. Where one of the goals is Rahmatan lil 'alamin. One of his commentaries is the Qur'an based on Jalalain's tafsir. This study uses a phenomenological approach with explanatory methods and triangulation data analysis, including data reduction, display and data verification, by looking at the phenomenon of Sam Poo Kong and Soen Ang Ing communities. The results showed that Islam and the relations of religions conveyed by Jalalain through his interpretation stated the 'recognition' of religions, while still emphasizing the internal doctrinal of Muslims. The community around Sam Poo Kong and Soen Ang Ing is a portrait of the progress of religious confession and the Muslim community carries out its religious activities well. The portrait of Islam and the relations of religions shown in the society of Sam Poo Kong and Soen Ang Ing is the realization of several verses in the Qur'an, such as Ali Imran 159; Ar-Rum 22; al-Hujurat 13; which if concluded is that a Muslim should be soft on the outside, the inside, and flexible over the existence of others.